Anatomical and functional assessment of Tryton bifurcation stent before and after final kissing balloon dilatation: Evaluations by three‐dimensional coronary angiography, optical coherence tomography imaging and fractional flow reserve. Issue 1 (27th August 2016) - Pyxaras, Stylianos A.; Toth, Gabor G.; Di Gioia, Giuseppe; Ughi, Giovanni J.; Tu, Shengxian; Rusinaru, Dan; Adriaenssens, Tom; Reiber, Johan H.C.; Leon, Martin B.; Bax, Jeroen J.; Wijns, William
Abstract : Objectives: To assess the anatomical and functional impact of final kissing balloon inflation (FKBI) after implantation of a dedicated bifurcation stent system. Background: Current evidence suggests clinical benefit of FKBI in patients undergoing bifurcation dilatation using the Tryton side branch stent (Tryton‐SBS). We hypothesized that FKBI improves anatomical reconstruction and functional results of bifurcation treated by Tryton‐SBS. Methods: An unselected group of patients with complex bifurcation coronary lesions undergoing percutaneous coronary intervention (PCI) with Tryton‐SBS underwent paired anatomical assessment with two‐ and three‐dimensional quantitative coronary analysis (2D‐ and 3D‐QCA), and optical coherence tomography (OCT), including 3D reconstruction before and after FKBI. Functional assessment by fractional flow reserve (FFR) was performed in the main branch (MB) and side branch (SB) before and after FKBI. Results: Paired pre‐ and post‐FKBI data were obtained in 10 patients. By OCT imaging, FKBI increased both the SB ostial area (4.93 ± 2.81 vs. 7.43 ± 2.87 mm 2, P < 0.001) and the SB maximum diameter (3.12 ± 0.98 vs. 3.82 ± 1.10 mm, P = 0.003). These findings were associated with a significant increase in FFR in the SB (0.90 ± 0.05 vs. 0.94 ± 0.03; P = 0.011), with no significant change in the MB (0.91 ± 0.05 vs. 0.92 ± 0.04; P = 0.470). Conclusions: In patients with complex bifurcation stenosis undergoing PCI with a dedicated bifurcation system, FKBI is associated with improved anatomical and functional results at the SB level, without compromising the result at the MB. © 2016 Wiley Periodicals, Inc.